THE EFFECTIVENESS OF TEACHER MANAGEMENT IN KUTTAB AL-FATIH EAST JAKARTA AS A NON-FORMAL EDUCATION INSTITUTION - Hidayatullah (Four Son Scholarship, 2023)
This study aims to describe the effectiveness of teacher management at Kuttab Al Fatih as a non-formal educational institution. This study aims to reveal: (1) Teacher management at Kuttab Al-Fatih East Jakarta, (2) Management of non-formal educational institutions, (3) Effectiveness of teacher management at Kuttab Al-Fatih as a non-formal educational institution. Research using qualitative research type, research data collection obtained by interview techniques, documentation, and observation. Based on the research findings regarding how effective the management of teachers is at Kuttab Al-Fatih, East Jakarta, it can be concluded that the management of teachers at Kuttab Al-Fatih, East Jakarta has been running effectively, this can be seen from the 4 indicators of effectiveness starting from the input indicators which include the characteristics teachers, facilities, equipment, and educational materials as well as management capacity, all of these components are available and running well. Likewise with process indicators which include administrative behavior, teacher time allocation, and student time allocation, the components in the process have been carried out properly by each party, especially teachers as executors in the field. For the output itself the author finds that the learning outcomes of students at Kuttab Al-Fatih are not yet 100% at each level, but in general it is very good for the results of student learning achievements, as well as changes in the attitudes and manners of students at Kuttab Al-Fatih Jakarta the East is very kind and this is reflected in their daily behavior from arrival to return. They always maintain etiquette, such as etiquette to teachers, etiquette to friends, etiquette in speaking, and other etiquette. As for the outcome indicators themselves, they can only be seen from the East Jakarta Kuttab Al-Fatih graduates who continue on to the next level of education.